Analisis Konsumsi BBM dengan Variasi Lingkungan Operasi Kendaraan Bermotor Menuju Perilaku Eco-Drive - Mohammad Syarifudin; Kemas Muhammat Abdul Fatah; Ruslan Dalimunthe (Infotekmesin, 2023)
An increase in greenhouse gases in the form of CO2 gas, a result of burning fuel in motorized vehicles, contributes to climate change. Technological approaches and the use of alternative fuels continue to be developed to reduce fuel consumption, but this is not enough. Another approach is eco-driving behavior. Replacing the air filter is one of the preventive maintenance activities on vehicles which is part of eco-driving behavior. This research intends to provide simple instructions for motorists so they can save fuel consumption. The results of the full-to-full test carried out 20 times can be a simple guide to eco-driving behavior, where the simple clue in question is the air filter replacement period. Replacing the air filter every 8,000 km and not every 16,000 km can save fuel consumption by 8% in the Krui area, 9% in the Tanjung Bintang area, and 6% in the Mesuji area.